Correction: Anemia in tuberculosis cases: A biomarker of severity? - Edson Beyker de Mendonça; Carolina AranaStanis Schmaltz; Flavia Marinho Sant'Anna; Alexandre Gomes Vizzoni; Daniela Palheiro Mendes-de-Almeida; Raquel de Vasconcellos Carvalhaes de Oliveira; Valeria Cavalcanti Rolla (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0245458.].